Evidence for Sexual Dimorphism in the Response to TLR3 Activation in the Developing Neonatal Mouse Brain: A Pilot Study - Chavez-Valdez, Raul; Mottahedin, Amin; Stridh, Linnea; Yellowhair, Tracylyn R.; Jantzie, Lauren L.; Northington, Frances J.; Mallard, Carina (Frontiers in Physiology, 2019)
Toll-like receptor (TLR)3 activation during the neonatal period produces responses linked to the origins of neuropsychiatric disorders. Although there is sexual dimorphism in neuropsychiatric disorders, it is unknown if brain responses to TLR3 activation are sex-specific. We hypothesized that poly I:C in a post-natal day (P)8 model induces a sexually dimorphic inflammatory responses. C57BL6 mice received intraperitoneal injection of poly I:C (10mg/kg) or vehicle (normal saline; NS) at P8. Pups were killed at 6h or 14h for caspase 3 and 8 activity assays, NFkB ELISA, IRF3, AP1 and GFAP western blotting and cytokines/ chemokines gene expression real time qRT-PCR (4-6/group).A second group of pups were killed at 24h (P9) or 7d (P15) after poly I:C to assess astrocytic (GFAP) and microglia (Iba1) activation in the hippocampus, thalamus and cortex using immunohistochemistry, and gene and protein expression of cytokines/chemokines using PCR and MSD, respectively (4-6/group). Non-parametric analysis was applied. Six hours after poly I:C, caspase-3 and -8 activities in cytosolic fractions were 1.6 and 2.8-fold higher in poly I:C-treated than in NS-treated female mice, respectively, and gene expressions of pro-inflammatory cytokines were upregulated in both sexes. After poly I:C, IRF3 nuclear translocation occurred earlier (6h) in female mice and later (14h) in male mice. At 14h after poly I:C, only male mice also had increased nuclear NFκB levels (88%, p<0.001) and GFAP expression coinciding with persistent IL-6 and FAS gene upregulation (110% and 77%, respectively; p<0.001) and IL-10 gene downregulation (-42%, p<0.05). At 24h after poly I:C, IL-1β, CXCL-10, TNF-α and MCP-1 were similarly increased in both sexes but at 7d after exposure, CXCL-10 and INFγ were increased and IL-10 was decreased only in female mice. Accordingly, microglial activation persisted at 7d after poly I:C in the hippocampus, thalamus and cortex of female mice. This preliminary study suggests the possibility that TLR3 activation may produce in the developing neonatal mouse brain a sexually dimorphic response with early activation of caspase-dependent pathways in female mice, activation of inflammatory cascades in both sexes, which then persists in female mice. Further well-powered studies are essential to confirm these sex-dependent findings.